Financial Monitoring in the field of Counter-Terrorism Financing at the European Level - Vnukova, N. (My University, 2023)
The report considers the main directions of development of financial monitoring in Ukraine and Hungary. FATF International Standard 6 strengthens the application of financial sanctions related to terrorist financing. Examples of financial investigations aimed at combating terrorist financing are given. An experiment was conducted to determine the interest in the topic of terrorism as one of the modern AML trends using the Google Trends search tool. Regions in Ukraine and Hungary with the largest number of requests are identified. Measurement data indicates that additional research is needed and it is possible to develop some kind of cross-border programs aimed at enhancing security.
Keywords: terrorism; financial monitoring; cross-border relations; Google Trends search engine